THE PERIOD COST CONCEPT FOR INCOME MEASUREMENT–CAN IT BE DEFENDED? - Fess, Philip E.; Ferrara, William L. (The Accounting Review, 1961)
The period cost concept divides cost data into two broad categories, firstly, "Period" costs which are those costs related to time, i.e., those costs which expire with the passage of time rather than with the volume of business activity, and secondly, "product" costs which include those costs which relate to the product being produced, i.e., those costs which are directly affected by the volume of business activity. Under the period cost concept as it relates to income measurement only variable manufacturing costs are considered inventoriable while fixed manufacturing costs as well as selling and administrative costs are period costs. In general the accounting profession does not accept for income measurement purposes the treatment of fixed manufacturing costs as period costs. Conversely the accounting profession has accepted for many years a period cost approach to the handling of selling and administrative costs. In this article the authors will show that the period cost concept is not appropriate for purposes of income measurement. It is the intention of this article to show that categorizations of cost such as period costs vs. product costs are not relevant to the process of income measurement.